2000
DOI: 10.1007/s004240000425
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic stimulation does not induce rhoA/ROCK-mediated Ca 2+ sensitization of the contractile element in chicken gizzard smooth muscle

Abstract: We have attempted to determine whether muscarinic stimulation induces RhoA/ROCK-mediated Ca2+ sensitization of contractions in chicken gizzard smooth muscles. rhoA is a small GTP-binding protein, and ROCK is a rhoA-associated coiled coil-forming serine/threonine kinase. The relationship between the cytosolic Ca2+ level ([Ca2+]i) and muscle force in the presence of a high K+ concentration was not different from that in the presence of carbachol. Verapamil inhibited muscle force in proportion to the decrease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 32 publications
3
18
1
Order By: Relevance
“…In embryonic smooth muscle, our results demonstrating a dose dependence of the inhibition of GTP␥S-induced force enhancement by the Rho-kinase inhibitor Y-27632 (Fig. 3) are similar to those of others (8,24,26). The magnitude of force enhancement was not affected by inhibition of MLCK or by inhibition of PKC with a concentration of staurosporine known to inhibit contractions of smooth muscle produced by phorbol esters (18).…”
Section: Force Versus Casupporting
confidence: 71%
See 1 more Smart Citation
“…In embryonic smooth muscle, our results demonstrating a dose dependence of the inhibition of GTP␥S-induced force enhancement by the Rho-kinase inhibitor Y-27632 (Fig. 3) are similar to those of others (8,24,26). The magnitude of force enhancement was not affected by inhibition of MLCK or by inhibition of PKC with a concentration of staurosporine known to inhibit contractions of smooth muscle produced by phorbol esters (18).…”
Section: Force Versus Casupporting
confidence: 71%
“…It is unclear why the results with GTP␥S in the adult gizzard are different in our study and that of Anabuki et al (24), but it could be because of the skinning techniques (25). In addition, Anabuki et al (24) showed a modest GTP␥S-induced force enhancement at only one [Ca 2ϩ ] level, and it may be that GTP␥S at other [Ca 2ϩ ] levels would not have produced a significant increase in force. Our data suggest that the diversity in the magnitude of agonist-induced force enhancement in smooth muscle tissues (8, 24) may be partially because of the relative expression of M133/M130, or splice-in/out MYPT isoforms.…”
Section: Force Versus Cacontrasting
confidence: 51%
“…This signaling pathway probably requires an intact cell membrane and thus would not be present in permeabilized and/or skinned preparations, explaining the absence of an effect of Rho-kinase inhibition on Ca 2ϩ activation of skinned smooth muscle strips. 18,19 However, Ca 2ϩ activation of Rho is consistent with the observations that in permeabilized vascular smooth muscle, Ca 2ϩ induces a translocation of Rho to the membrane 20 and the inhibition of force produced by depolarization when Rho is inactivated. 21 It has been demonstrated that the magnitude of the change in MLC 20 phosphorylation produced by depolarization is less than that produced by agonist stimulation for any given level of intracellular Ca 2ϩ .…”
supporting
confidence: 74%
“…In the ileum, ROK blockade by Y-27632 and HA-1077 leaves the phasic component nearly intact and abolishes the tonic component (185), whereas in the bladder, both components are greatly diminished (79). Although GTP␥S induces ROK activation and Ca 2ϩ sensitization in chicken gizzard smooth muscle, muscarinic receptor stimulation does not cause ROK-dependent Ca 2ϩ sensitization in this muscle type (6). However, Y-27632 reduces stomach antrum motility in conscious rats (197) and stomach fundus contraction induced by muscarinic receptor activation in vitro (156).…”
Section: Rok and Pkc Participate In Elevating Ca 2؉ Sensitivity Of Mamentioning
confidence: 81%